The Effectiveness of the Blended Learning Model in Indonesian Language Learning - Muh. Safar (PT. Anagata Sembagi Education, 2026)
The transformation of Indonesian language learning in the digital era requires innovative instructional models that effectively enhance students’ literacy skills. Blended learning, which integrates face-to-face instruction with online learning components, has emerged as a promising approach to address declining literacy performance and changing communication patterns. This study aimed to analyze the effectiveness of the blended learning model in improving students’ Indonesian language skills. A quasi-experimental design with a pretest–posttest control group was employed. The participants consisted of elementary school students divided into an experimental group receiving blended learning treatment and a control group receiving conventional instruction. Data were collected through standardized language proficiency tests covering reading, writing, speaking, and listening skills. The results revealed a significant difference between the experimental and control groups, with the experimental group demonstrating higher posttest scores and a large effect size. These findings indicate that a structured and contextually designed blended learning model significantly enhances students’ language competence. In conclusion, blended learning provides an effective and sustainable instructional strategy for Indonesian language education in the digital era, particularly when supported by adequate infrastructure and systematic instructional design.